Les activités sidérurgiques dans les campagnes du Gharb al-Andalus : l’exemple de la vallée du Mira (Bas Alentejo, sud du Portugal) - Mathieu Grangé; Jorge Vilhena (Revue des Mondes Musulmans et de la Méditerranée)
In the present paper, based on recent archaeological work carried out in the River Mira valley, the authors intend to ask some questions related to the exploration of ferrous ressources in rural environment in the Gharb al-Andalus. Different themes are treated, as the origine and nature of raw materials, the siderurgical technics employed, the different stages of the ‘chaîne opératoire’ represented on the rural settlements, and the organization of production and distribution of the siderurgical products, probably limited to iron blooms destinated to circulation (trade? tax paying?). Most of the data concern the 9th century, but the documentation now available presents some methodological problems, which are also referred to by the authors.